تطبيق طريقة لعبة Make and Match لترقية مهارة القراءة لدى طالبات في المدرسة الدينية الوسطى بمعهد دار الفلاح الإسلامي الخامس جوكير جومبانج - Laila Kamila Hanum; Fathur Rohman (Sekolah Tinggi Ilmu Tarbiyah Al-Hilal Sigli Aceh- Indonesia, 2025)
At Darul Falah 5 Islamic Boarding School in Jombang, many first-year students still struggle with reading Arabic texts and understanding their meanings accurately. Their enthusiasm for learning Arabic reading is low, largely due to traditional, non-interactive teaching methods that lead to passive learning. In response, the researcher conducted a qualitative case study titled